SKI AND SNOWBOARD SCHOOL PROGRAMS: INCIDENCE OF GRADE-SPECIFIC INJURY. Issue 4 (1st February 2017) - Djerboua, Maya; Sran, R; Mitra, T; Russell, K; White, K; Goulet, C; Emery, CA; Hagel, BE
Abstract : Background: Participating in school sanctioned skiing and snowboarding programs is a great way to encourage physical activity in youth. However, there is little evidence on the rates of ski and snowboard injuries in school programs. This information is important to inform guidelines on appropriate activities for school physical education programs. Objective: To evaluate incidence of grade group-specific ski and snowboard-related injuries. Design: Historical cohort study. Setting: Ski and snowboard school programs hosted at a ski area in Southern Alberta, Canada. Participants: Students partaking in skiing/snowboarding during the 2013–2014 season at a ski area in Southern Alberta (N=16260 visits). Assessment of Risk Factors: Risk factors observed include grade (1–3, 4–6, 7–12), ability (self-rated skill level), sex, activity and socioeconomic status (SES). Main Outcome Measurements: Injury rates and injury severity. Injury information was extracted from Accident Report Forms completed by the ski patrol. Severe injuries were defined as patient final destination listed as hospital. Rate denominator data were obtained from school enrolment forms. Results: Forty of 107 (24%) injuries reported to the ski patrol were severe. Adolescents (grade 7–12) were found to have a higher crude rate of injury (91/10, 000 visits) than children (grades 1–3: 25/10, 000 visits; grades 4–6: 25/10, 000 visits). When adjusted for other observed risk factors (sex, activity, ability and SES) no significant differences were found for rate of injury between the three grade groups (1–3, 4–6 and 7–12). No severe injuries were observed in the grade 1–3 group. Conclusions: Results indicate that participants in the grade 1–3 group had the lowest crude and adjusted rate of injury and did not sustain any severe injuries. Respectively, the grade 7–12 group had the highest rate of crude injury, both overall and severe. These results will help inform ski and snowboard programs and safety guidelines for physical activity programs in schools.